Chemical quality indices in local and imported beef meat - HASSANIEN, F. S.; SHALTOUT, F. A.; FAHMEY, M. Z.; ELSUKKARY, H. F. (Journal of the Hellenic Veterinary Medical Society, 2021)
Freshness of meat samples can be measured and evaluated by chemical tests based on t h e i r protein decomposition, lipid oxidation and/or pH values. A total of 100 random samples of local and imported beef meat (50 of each) were collected from different shops in Cairo governorate for evaluation of their chemical quality. Chemical examination of beef samples revealed that the mean values of pH, TVB/N (mg%) and TBA (mg/Kg) were 5.77 ± 0.32, 11.9±1.63 &0.58± 0.10 for local meat samples respectively , while they were 6.6 ± 0.12, 21.5 ± 1.95 & 0.95 ± 0.11 for imported samples respectively. Overall results obtained were considered important meat quality indicators. It is clear that there is a significant difference between fresh and frozen meat samples, which could be attributed to storage time and other conditions, particularly for frozen samples.